State feedback control of linear systems - A renewed approach - Roppenecker, Günter (At-Automatisierungstechnik, 2009)
Summary The standard structure for state feedback control of linear systems so far used consists of a state feedback control law and a static prefilter to feed in the reference input. Unlike the proved structure of classical control systems it does not show a comparison of the reference input and the corresponding plant signal, and its prefilter depends on the state feedback controller. In this paper it is shown that the standard structure for state feedback control can also be transferred into an alternative structure which reveals a comparison of reference and corresponding plant signals, and in addition allows a feedforward path for reference input and disturbance injection which now proves to be independent of the controller. Finally it results that state feedback control can always be realized in the common structure of classical control systems as well. Hereby using a model-based feedforward controller the design of the reference input behaviour, of the reaction on measured disturbances and of the feedback controller to reject the remaining influences can be done separately. © Oldenbourg Wissenschaftsverlag.
Keywords: Linear systems; Model-based feed forward control; State feedback control